Peel-off Kefir Mask Arachi (Arachis hypogaea L.): Characterization and Antioxidant Activity - Amalia Khairunnisa; Pratika Viogenta; Nani Kartinah; Fathur Rahman; Mulia Mulia (Borneo Journal of Pharmacy, 2022)
This study aims to determine the best formulation for the peel-off mask Arachi or peanut (Arachis hypogaea L). Arachis hypogaea kefir as an active ingredient is added with variations in the concentration of F1 (0.5%) and F2 (2%) (w/v). Organoleptic tests, homogeneity, dry time, and pH were carried out on the peel-off mask that had been made. Antioxidant test (DPPH methods) was performed on masks F1 and F2. The results showed that the peel-off mask of A. hypogaea kefir had the best antioxidant activity at a concentration of 2% (F2) kefir with an IC50 value of 1.865 ppm and was very active. The characteristics of the peel-off mask have good physical stability, proven by not experiencing a change in color, odor, being homogeneous, having good dispersion power, and having a dry time ranging from 10-23 minutes. The pH value of the peel-off mask preparation is 4.52, and it is appropriate with SNI and the pH balance of normal human skin. The peel-off mask of A. hypogaea kefir can be produced because has good physical stability and antioxidant activity.